PENGARUH CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING ( Studi Kasus Pada Pelanggan McDonald’s MT Haryono) - Uun Nur Laila; N. Rachma; Ahmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT This research target is to know and analyse influence of brand image directly to satisfaction, influence brand image directly to loyalitas, influence satisfaction directly to loyalitas, influence brand image to loyalitas through satisfaction as intervening variable, influence of quality service directly to satisfaction, influence quality service directly to loyalitas, and influence quality service to loyalitas through satisfaction as intervening variable at customer of McDonald’s MT Haryono Malang.Result of research indicate that there are direct influence brand image directly to satisfaction 0,611. influence brand image directly to loyalitas 0,581, influence satisfaction directly to loyalitas 0,567, influence brand image to loyalitas through satisfaction as intervening variable 0,346, influence of quality service directly to satisfaction 0,533, influence quality service directly to loyalitas 0,524, and influence quality service to loyalitas through satisfaction as intervening variable 0,302 at customer of McDonald’s MT Haryono Malang. Keyword :brand image, quality servive, satisfaction and loyality